A CONCEPTUAL PAPER ON THE PRECURSORS OF EMPLOYABILITY SKILLS OF GIATMARA GRADUATES IN MALAYSIA - Hasnun Anip Bustaman; Norsuhaila Ramli; Siti Maziah Ab Rahman; Rikinorhakis Ridzwan (International Journal of Accounting, Finance and Business, 2024)
This conceptual paper aims to investigate the precursors of employability skills among graduates of GIATMARA, a vocational training institution in Malaysia. By drawing upon existing literature from vocational education, human resource management, and employability studies, we seek to establish a comprehensive framework that sheds light on the factors influencing the development of employability skills among GIATMARA graduates. The study begins by examining the historical roots and contemporary practices of vocational education in Malaysia, emphasizing its role in addressing the skills gap and promoting economic growth. We then explore the concept of employability skills, defining its key components and highlighting its importance in enhancing graduates' job prospects and career advancement. The subsequent sections analyze various factors influencing the development of employability skills among GIATMARA graduates, including the quality of training, the relevance of the curriculum, the effectiveness of teaching methods, and the role of industry partnerships. It takes employability skills to survive in the technological age. Employers discover, however, that job seekers lack certain knowledge and skills. As graduates get ready to enter the job market, employability skills are critical. The study sought to determine the impact of knowledge and skills on employability among Malaysian graduates of technical and vocational education and training. To finish the study, respondents who had graduated from GIATMARA were chosen. The sample size was chosen using simple random. Descriptive statistics like frequency, mean, and standard deviation were used in the quantitative data analysis of this study's data. Data was gathered using questionnaires that were modified to align with the study's goal after being lifted verbatim from a few other studies. Individuals served as the research study's unit of analysis. The science direct and Scopus databases were the primary sources of references for the literature reviews in this study. The information from the literature review's implications was given, and it suggested several frameworks for GIATMARA to enhance its graduates' employability. The findings were discussed and presented by the research questions. The framework highlights the significance of knowledge and skills related to the GIATMARA curriculum for the creation of GIATMARA graduates who are employable and competitive in Malaysia. In conclusion, this paper proposes several avenues for future research aimed at refining our theoretical model and developing practical recommendations for policy makers, educators, and employers seeking to foster greater levels of employability among GIATMARA graduates. These include exploring innovative teaching methods, leveraging technology to enhance learning outcomes, and fostering collaborative partnerships between stakeholders. Ultimately, it is hoped that this work will contribute towards a more robust and sustainable vocational education system in Malaysia, one that better serves the needs of graduates and the wider economy.